Tbx1 regulates the BMP-Smad1 pathway in a transcription independent manner. - F Gabriella Fulcoli; Tuong Huynh; Peter J Scambler; Antonio Baldini (PLoS ONE)
Tbx1 is a T-box transcription factor implicated in DiGeorge syndrome. The molecular function of Tbx1 is unclear although it can transactivate reporters with T-box binding elements. We discovered that Tbx1 binds Smad1 and suppresses the Bmp4/Smad1 signaling. Tbx1 interferes with Smad1 to Smad4 binding, and a mutation of Tbx1 that abolishes transactivation, does not affect Smad1 binding nor does affect the ability to suppress Smad1 activity. In addition, a disease-associated mutation of TBX1 that does not prevent transactivation, prevents the TBX1-SMAD1 interaction. Expression of Tbx1 in transgenic mice generates phenotypes similar to those associated with loss of a Bmp receptor. One phenotype could be rescued by transgenic Smad1 expression. Our data indicate that Tbx1 interferes with Bmp/Smad1 signaling and provide strong evidence that a T-box transcription factor has functions unrelated to transactivation.